Captivity, uprooting and survival of a Castilian Mudejar community: Deza (1429) (Edad Media. Revista de Historia, 2025)
At the beginning of 1429, Alfonso V of Aragon reached an agreement with Infante Enrique of Castile and King Juan of Navarre to organize an army and carry out a military incursion into Castile. Their objective was to pressure the Castilian monarch, Juan II, to restore the power of the Aragonese infantes in the government of the kingdom. This article analyzes one of the military operations carried out by this army, specifically, the attack perpetrated against the town of Deza, located in the easternmost part of the Crown of Castile. The key event to be presented is the aggression suffered by the Islamic community of this town, whose members were captured and put up for sale in Zaragoza and other cities of the Crown of Aragon. The impact of this event in the local context was already highlighted in some of the chronicles of the 15th and 16th centuries, although, in this work, we will primarily rely on unpublished documentation from the Archive of the Crown of Aragon and the Historical Archive of Notarial Protocols of Zaragoza.
Keywords: Late Middle Ages; Kingdom of Aragón; Muslims; War; Captivity; Slavery